Analysis of Guest Satisfaction Level on Service Efficiency and Responsiveness by Pool Bar Staff at Mandapa, A Ritz-Carlton Reserve Ubud, Bali - Putri, Ni Putu Widya; Widhiastuty, Ni Luh Putu Sri; Tianingrum, Ni Nyoman Nidya (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2026)
In ultra-luxury hotel operations, guest satisfaction is closely linked to service efficiency and staff responsiveness. This study aims to analyze how Pool Bar staff maintain service efficiency and responsiveness toward guest satisfaction at Mandapa, A Ritz-Carlton Reserve Ubud, Bali; identify the challenges encountered; and describe the solutions implemented. A qualitative descriptive approach was employed, with data collected through observation, interviews with five Pool Bar staff members, and documentation during January–March 2025. The results reveal that Pool Bar staff consistently implemented the Leading Quality Assurance (LQA) standard across all 24 service indicators—from welcoming guests within one minute, presenting menus and taking orders within five minutes, serving beverages within five to eight minutes and food within fifteen to twenty minutes, to providing proactive check-backs and farewell. The challenges identified include varying guest character preferences in a public area, increased workload during high season, and difficulty monitoring guest movement in the open area. Solutions applied include flexible area management with kids pool and main pool designation, pre-shift line-up with clear task delegation, cross-team awareness, and anticipatory service. This study concludes that consistent LQA implementation, supported by strong team coordination and proactive service, significantly contributes to guest satisfaction at Pool Bar.